Bilateral Glaucoma as Possible Additional Feature for PGAP3-Associated Hyperphosphatasia - Osama Obaid; Reem Batawi; Heba Alqurashi; Thana Ewis; Ahmad A. Obaid (Case Reports in Genetics)
Hyperphosphatasia with mental disorder (HPMRS) is a rare autosomal recessive disease caused by gene mutations in enzymes involved in the synthesis and remodeling of lipids. Seven-month-old boy diagnosed with bilateral glaucoma had a cleft palate, facial dysmorphism, hypertelorism, a broad nasal bridge, and large fleshy earlobes. A brain MRI scan also revealed brain abnormalities. The observed phenotype in a seven-month-old boy is in agreement with the phenotypic features of HPRMS type-4. Whole exome sequencing revealed a possible pathogenic variant of PGAP3 in a homozygous state (c.320C > T, p.Ser107Leu) which supported the diagnosis of HPRMS type-4. We report an unusual presentation for HPMRS and suggest adding this syndrome to the list of differential diagnoses of syndromic congenital glaucoma.